Manifestation of Ideology and Power in Matthew’s Parables: Investigation of Appraisal in View of Critical Discourse Analysis - Cahya, Neiva; Henrikus Joko Yulianto; Katharina Rustipa (English Education Journal, 2024)
This topic was chosen because the researchersant to know which appraisal is dominant in Matthew's parables. According to Martin & White (2005), appraisal studies determine how Matthew evaluates what Jesus said in the Bible, especially in the parables. The researcher wants to know how Jesus used parables to teach his disciples. Why could the disciples understand what Jesus said, and why is using parables a powerful way to teach about the Kingdom of God. This study also focuses on the ideology and power with which Jesus used parables to teach his disciples. Based on this theory, ideology can be analyzed using appraisal studies, which include the analysis of affect, judgments, and appreciation. Therefore, this study aims to explore the manifestations of ideology and power by examining the evaluative study in Jesus' parables based on Matthew's writings. In this study, the researchers will collect data using an observation guide. Therefore, there are no actual participants who took part in this study. The data results and discussion on the Gospel of Matthew macro genre indicate it is a narrative text.